PENGARUH AKUNTANSI PERTANGGUNGJAWABAN DAN PARTISIPASI ANGGARAN TERHADAP EFEKTIVITAS PENGENDALIAN BIAYA PRODUKSI - Kadek Ari Widianti; Made Yudi Darmita; Ni Nyoman Sri Rahayu Trisna Dewi (Universitas Triatma Mulya, 2023)
The reason for this study was to decide the impact of liability bookkeeping and spending plan interest on the adequacy of creation cost control at PT Medina Debeuz Indah. This kind of exploration utilizes a quantitative methodology. The populace in this study were 37 individuals. Examining utilizing immersed testing technique. This is done on the grounds that the populace is moderately little. The example in this study was that all individuals from the populace were tested, specifically supervisors and staff of the money and bookkeeping division, so an example size of 37 individuals was gotten. The information examination strategies utilized are clear measurements, legitimacy and unwavering quality tests, old style suppositions, different straight relapse, fractional t factual tests utilizing the SPSS application. The consequences of this study show that to some extent responsibility bookkeeping affects the viability of creation cost control. While Spending plan Investment fundamentally affects the Viability of Creation Cost Control.